2019
DOI: 10.1007/s00122-019-03276-6
|View full text |Cite
|
Sign up to set email alerts
|

Training population selection and use of fixed effects to optimize genomic predictions in a historical USA winter wheat panel

Abstract: Key message The optimization of training populations and the use of diagnostic markers as fixed effects increase the predictive ability of genomic prediction models in a cooperative wheat breeding panel. Abstract Plant breeding programs often have access to a large amount of historical data that is highly unbalanced, particularly across years. This study examined approaches to utilize these data sets as training populations to integrate genomic selection into existing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 51 publications
13
100
2
Order By: Relevance
“…Overall, results from our study were encouraging regarding the prediction of preliminary lines, even for highly polygenic and complex traits like yield and test weight. The model's predictive ability, with cross validation, showed moderate to high accuracies for the different traits, in agreement with previous studies on wheat [11,13,15,[26][27][28].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, results from our study were encouraging regarding the prediction of preliminary lines, even for highly polygenic and complex traits like yield and test weight. The model's predictive ability, with cross validation, showed moderate to high accuracies for the different traits, in agreement with previous studies on wheat [11,13,15,[26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Isidro et al [13] applying different strategies to define the TP, obtained for wheat populations with a mild population structure, prediction accuracies ranging from 0.2-0.5, noting an increase of prediction accuracy with increases in TP size. Recently, Sarinelli et al [15] obtained prediction accuracies ranging from 0.4 to 0.6 under different methods of selecting the TP and different TP sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Galiano-Carneiro et al [38] previously observed improved accuracy for Fusarium head blight-related traits in winter triticale (× Tritosecale) through fitting significant markers with >5% genetic variance as fixed effect in a weighted ridge regression model. Maximum gains in accuracy were also observed when combinations of multiple height and phenology genes were included as fixed effects in a prediction model for yield in a historical US winter-wheat panel [39].…”
Section: Genomic Prediction For Grain Yieldmentioning
confidence: 93%